2016
DOI: 10.1111/cas.13088
|View full text |Cite|
|
Sign up to set email alerts
|

Zebularine enhances apoptosis of human osteosarcoma cells by suppressing methylation of ARHI

Abstract: ARHI is an imprinted tumor suppressor gene and its methylation suppresses ARHI transcription levels to cause the development and progression of malignant tumors. Zebularine exerts a demethylation function for tumor suppressor genes. Our study aims to investigate the effect and mechanism of action of zebularine on the epigenetic modification of the ARHI gene, and whether this effect may modulate the viability and apoptosis of human osteosarcoma cells. We found that zebularine inhibited the viability and promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Moreover, miR-10b overexpression and HOXA1 knockdown resulted in aberrant DNMT expression and an increased embryo apoptosis ratio. Previous findings in human cancer cells have shown that cell apoptosis and cell proliferation are related to DNA methylation, and DNA methylation can help inactivate apoptotic pathways at several points (Cho et al, 2011; Ye et al, 2016; Costa et al, 2017; Loginov et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-10b overexpression and HOXA1 knockdown resulted in aberrant DNMT expression and an increased embryo apoptosis ratio. Previous findings in human cancer cells have shown that cell apoptosis and cell proliferation are related to DNA methylation, and DNA methylation can help inactivate apoptotic pathways at several points (Cho et al, 2011; Ye et al, 2016; Costa et al, 2017; Loginov et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…DNA demethylation agents and/or histone deacetylation inhibitors can recover DIRAS3 activity in breast and ovarian cancers (Badgwell et al 2011 ). Suppressing methylation of DIRAS3 by Zebularine can elevate DIRAS3 expression and enhances apoptosis in osteosarcoma cells (Ye et al 2016 ). In addition, DNA over-methylation occurs in 79.1% of GC tissue with deficient DIRAS3 expression (Wang et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that miR-221 promotes tumor development, while ARHI is a tumor suppressor gene [Chen et al, 2011;Li et al, 2013b;Ye et al, 2015Ye et al, , 2016. We transfected miR-221 mimics and si-ARHI into GAS5-overexpressing MG-63 cells to investigate the role of miR-221 and ARHI on cell proliferation, migration, and EMT of osteosarcoma cells.…”
Section: Gas5 Suppresses Cell Proliferation Migration and Emt Via Regulating Mir-221 And Arhi Expression In Osteosarcoma Cellsmentioning
confidence: 99%